PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN TAMU MENGINAP DI TJOKRO STYLE HOTEL YOGYAKARTA - Susanti, Erma; Wulansari, Nidia (Ensiklopedia of Journal, 2023)
Abstract: Research conducted while carrying out a certified internship at Tjokro Style Hotel Yogyakarta, the quality of service provided by the hotel was low and the location of the hotel was narrow so that it disrupted activities. This research was conducted aiming to determine the effect of service quality and location on guest satisfaction staying at Tjokro Style Hotel Yogyakarta. This type of research is causal associative, to determine the effect of service quality (X1), location (X2) on guest satisfaction (Y) staying at Tjokro Style Hotel Yogyakarta. The population is guests who have stayed at Tjokro Style Hotel Yogyakarta, are over 17 years old and are not corporate or group tour guests. The sample is 98 respondents, using a sample technique that is purposive sampling. Primary and secondary data collection, namely the distribution of questionnaires and can be directly from the hotel. Hypothesis testing uses Multiple Linear Regression tests, using SPSS version 26.00. The results of the study are: (1) Service Quality in the good category (79%) (2) Location in the good category (70%) (3) Guest satisfaction (53%). Test the Multiple Linear Regression hypothesis with a calculated F value of 9.303 with a significance of 0.000 <0.05, where the service quality and location variables have a significant effect on guest satisfaction, with an Adjust R Square value of 0.146. Has a significant relationship to the three variables.Keywords: Service Quality, Location and Guest Satisfaction.